Lack of Protection for Non-Fungible Token (NFT) Creators in Indonesia: A Progressive Legal Study: Kurangnya Perlindungan Pencipta Non-Fungible Token (NFT) di Indonesia: Suatu Kajian Hukum Progresif - Norasari, Dina Aidah (Rechtsidee, 2022)
This article presents a normative legal research that aims to provide legal protection guarantees for creators of Non-Fungible Token (NFT) works from a progressive legal perspective. The research used a statutory approach and concept approach to examine the implications of NFT on the existing legal framework. The results confirm that NFT requires special regulations to protect creators' rights, including revising the Copyright Law and developing regulations to affirm NFT's character. The study recommends that NFT works be included in copyright through extensive and futuristic interpretation, and the government's legal policy should specifically regulate NFT and issue certificates of NFT works to ensure legal protection and certainty. Overall, this research highlights the need for proactive legal responses to technological developments such as NFT, which can have economic value and require legal protection.Highlights: Non-Fungible Tokens (NFT) require special legal protection for creators due to their economic value. Revising Copyright Law and developing regulations to affirm NFT's character are recommended. NFT works should be included in copyright through extensive interpretation and the government should issue certificates of NFT works to ensure legal protection and certainty.